2023
DOI: 10.3390/molecules28166104
|View full text |Cite
|
Sign up to set email alerts
|

Oil-Contaminated Soil Remediation with Biodegradation by Autochthonous Microorganisms and Phytoremediation by Maize (Zea mays)

Katarzyna Wojtowicz,
Teresa Steliga,
Piotr Kapusta
et al.

Abstract: Biological methods are currently the most commonly used methods for removing hazardous substances from land. This research work focuses on the remediation of oil-contaminated land. The biodegradation of aliphatic hydrocarbons and PAHs as a result of inoculation with biopreparations B1 and B2 was investigated. Biopreparation B1 was developed on the basis of autochthonous bacteria, consisting of strains Dietzia sp. IN118, Gordonia sp. IN101, Mycolicibacterium frederiksbergense IN53, Rhodococcus erythropolis IN11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 128 publications
0
15
0
Order By: Relevance
“…The bacterial and fungal strains used in the microbial consortia had proven abilities to metabolize petroleum hydrocarbons and did not exhibit pathogenic properties. A detailed description of the design of microbial consortia B1 and B2, along with the method of identification of the strains of bacteria and fungi present in them, is provided in a previous article [17]. More information about the microbial consortia used in the research is available in Supplementary Materials.…”
Section: Soil Microbial Consortia γ-Pga and Plant Descriptionmentioning
confidence: 99%
See 3 more Smart Citations
“…The bacterial and fungal strains used in the microbial consortia had proven abilities to metabolize petroleum hydrocarbons and did not exhibit pathogenic properties. A detailed description of the design of microbial consortia B1 and B2, along with the method of identification of the strains of bacteria and fungi present in them, is provided in a previous article [17]. More information about the microbial consortia used in the research is available in Supplementary Materials.…”
Section: Soil Microbial Consortia γ-Pga and Plant Descriptionmentioning
confidence: 99%
“…It has been proven that aged soils containing a greater variety of contaminants, with higher concentrations of xenobiotics, undergo the treatment process more slowly than freshly contaminated soils with a single type of contaminant. For real soils with a wide spectrum of contaminants, the efficiency of phytoremediation alone may be too low [17]. Therefore, it is critical to find a new, efficient and economically beneficial approach to the phytoremediation process.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Remediation techniques were widely studied for oil removal in soils [10] [11], [12] have removed 12-22% of oil content in soil samples using organomineral sorbents like biofertilizer and aluminum alloys activated by tin, gallium, and indium, besides phytotoxicity decreased with the treatment. Wojtowicz et al [13] have reached 31% of biodegradation using autochthonous bacteria and fungi inoculation, and Zhao et al [14] observed 52% removal of crude oil due to bacterial consortium when for a 60-day period. Ambaye et al [15] and Michael-Igolima et al [16] have reviewed the challenges and perspectives over hydrocarbon-contaminated soil remediation aspects, and highlighted nanotechnologies and biosolutions as emerging technologies, linked to thermal desorption [8], electrochemical methods, advanced oxidation processes [17] [18], and permeable active barriers [19] [20] [21] [22].…”
Section: Introductionmentioning
confidence: 99%